Unusual morphological presentation of cutaneous malignant melanoma: A rare case report - Gaurav Dash; Swetalina Pradhan; Subhasini Naik (Indian Dermatology Online Journal, 2021)
Cutaneous malignant melanoma is a rapidly progressing skin tumor accounting for most deaths from skin malignancies. Four morphological variants (nodular, superficial spreading, lentigo maligna, and acral lentiginous) are described in the literature. Here we are reporting malignant melanoma in a 35-year-old male who presented with depigmented plaques with few hyperpigmented areas and extensive overlying scaling. The patient progressed to the nodular stage within 2 weeks and succumbed to death during chemotherapy. We are reporting such rare presentation of malignant melanoma to create awareness among dermatologists to avoid misdiagnosis and delayed treatment which can lead to rapid progression and fatal outcome.